2019
DOI: 10.1177/1744987119839453
|View full text |Cite
|
Sign up to set email alerts
|

Assessing nurses’ informatics competency and identifying its related factors

Abstract: Background Due to the increasing use of informatics as an infrastructure in developing the quality of care and patient safety, informatics competency has become a crucial requirement for nurses. Aim This study was conducted to assess nursing informatics competency, and identify related factors in registered nurses. Method This research is an analytical descriptive study in which the research community included 205 nurses working at Tabriz University of Medical Sciences’ hospitals. The researcher-made questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 15 publications
2
25
0
4
Order By: Relevance
“…The NI competency of the intervention group promoted from "competent" level in pretest to "proficient" level after the training program. Several studies in different countries reported that nurses' NI competency was at the competent level before attending any educational intervention [13,[33][34][35][36]. However, other studies indicated that nurses' NI competency was low [14,37,38].…”
Section: Principal Resultsmentioning
confidence: 99%
“…The NI competency of the intervention group promoted from "competent" level in pretest to "proficient" level after the training program. Several studies in different countries reported that nurses' NI competency was at the competent level before attending any educational intervention [13,[33][34][35][36]. However, other studies indicated that nurses' NI competency was low [14,37,38].…”
Section: Principal Resultsmentioning
confidence: 99%
“…The NI competency of the intervention group promoted from "competent" level in pretest to "pro cient" level after the training program. The results of several studies in different countries reported that nurses' NI competency was at the competent level before attending any educational intervention [33][34][35][36][37]. However, other studies indicated that nurses' NI competency was within the range of low level of competency [15,38,39].…”
Section: Principal Resultsmentioning
confidence: 99%
“…The NI competency of the intervention group promoted from "competent" level in pretest to "pro cient" level after the training program. Several studies in different countries reported that nurses' NI competency was at the competent level before attending any educational intervention [33][34][35][36][37]. However, other studies indicated that nurses' NI competency was low [14,38,39].…”
Section: Discussionmentioning
confidence: 99%